2019
DOI: 10.1073/pnas.1905721116
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal alternative splicing of GluN1 regulates the maturation of excitatory synapses and seizure susceptibility

Abstract: The majority of NMDA receptors (NMDARs) in the brain are composed of 2 GluN1 and 2 GluN2 subunits. The inclusion or exclusion of 1 N-terminal and 2 C-terminal domains of GluN1 results in 8 splicing variants that exhibit distinct temporal and spatial patterns of expression and functional properties. However, previous functional analyses of Grin1 variants have been done using heterologous expression and the in vivo function of Grin1 splicing is unknown. Here we show that N-terminal splicing of GluN1 has importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…This splicing change is consistent with an excitatory phenotype, because expression of this exon leads to slower desensitization of AMPA receptors, increasing susceptibility to excitotoxicity (Koike et al, 2000; Pei et al, 2009). We also identified increased exclusion of GRIN1 exon 5 in tau-V337M organoids, which has been associated with the overproduction of excitatory synapses in layer V pyramidal neurons in adult mice that in turn increases seizure susceptibility (Liu et al, 2019), and may contribute to the cortical layer vulnerability observed in our model and in FTD brain.…”
Section: Discussionmentioning
confidence: 64%
“…This splicing change is consistent with an excitatory phenotype, because expression of this exon leads to slower desensitization of AMPA receptors, increasing susceptibility to excitotoxicity (Koike et al, 2000; Pei et al, 2009). We also identified increased exclusion of GRIN1 exon 5 in tau-V337M organoids, which has been associated with the overproduction of excitatory synapses in layer V pyramidal neurons in adult mice that in turn increases seizure susceptibility (Liu et al, 2019), and may contribute to the cortical layer vulnerability observed in our model and in FTD brain.…”
Section: Discussionmentioning
confidence: 64%
“…Interestingly, the Grin1 gene gives rise to 8 splice variants and recently it has been shown that the selective expression of different GluN1 isoforms determines long-term potentiation in the hippocampus and spatial memory performance [ 67 ]. Moreover, the relative abundance of some spliced isoforms of GluN1 subunit is associated with increased seizure susceptibility in adult mice [ 68 ]. Taken together, these findings suggest that altered alternative splicing events observed in MeCP2-shRNA mice at baseline might impact proper neuronal function and consequently contribute to cognitive deficits and excitation/inhibition imbalance reminiscent of RTT.…”
Section: Discussionmentioning
confidence: 99%
“…GluN1 splice variants are differentially expressed in various types of neurons, across different brain regions, and throughout distinct development stages [6][7][8][9]. N-terminal splicing affects NMDAR channel gating kinetics [10][11][12], as well as modulation by pH, Zn 2+ , extracellular polyamines [13] and long-term synaptic potentiation [14]. Many important properties of NMDA receptors such as glycine and glutamate potency, and voltage-dependent blockade by Mg 2+ are unaffected by the presence of N1 insert [4,5,15].…”
Section: Discussionmentioning
confidence: 99%